Analysis of Ex Disposal Area Land Use For Agriculture Activity and Mangrove Ecosystem in Segara Anakan Regency Based on Geography Information System - Churun A’in; Subiyanto Subiyanto; Agus Hartoko (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2010)
The aim of research was to study potential land location and width of EDA as agriculture activity and mangrove ecosystem, based on land suitability. The research methode was descriptive case study and sampling method used was purposive sampling, including 2 sampling periods (rainy and dry season). The location in this research was Ex Disposal Area (EDA), consist of Klaces, Panikel and Ujunggagak district were involved. Research variabel are soil quality (land quality), water quality and EDA’s environment parameters. Analysis data using GIS, proccess by ER Mapper 7,0 and ArcGIS 9,3 software. The concept of suitability level by scoring method combining values and weight variable. Result of esearch showed that potential land for fisheries activity (pond land) are: moderately suitable class (S2) is 5,309.05 m2, include Panikel and Ujunggagak district; marginally suitable class (S3) is 77,325.77 m2, not suitable for present time class (N1) is 1,365,955.67 m2, and permanently unsuitable class (N2) is 7,583,809.51 m2. S3, N1,N2 class were found in Panikel, Klaces and Ujunggagak district. Potential land for agriculture activity (rice field) are : moderately class (S2) is 2,051,725.30 m2; marginally suitable class (S3) is 54,083.03 m2, width of not suitable for present time class (N1) is 2,416,591.48 m2, and permanently unsuitable (N2) is 4,510,000.20 m2. Fourth classes of potential land for agriculture activity (farming land) exist in Panikel, Klaces and Ujunggagak district. Potential land for mangrove ecosystem are : marginally suitable class (S3) is 401.64 m2, found in Ujunggagak district ; not suitable for present time class (N1) is 1,046.59 m2, include Panikel dan Ujunggagak district, and permanently unsuitable class (N2) is 9.030.951,77 m2. This class are found in Panikel, Klaces and Ujunggagak district. Key Words : Land Use, EDA, GIS.